Enhanced selectivity of 3-D ordered macroporous Pt/Al2O3 catalysts in nitrites removal from water - Sekhar, A. C. Sunil; Zaki, A.; Troncea, S.; Casale, S.; Vinod, C. P.; Dacquin, J. P.; Granger, P. (Applied Catalysis A-General, 2018)
Tailored macroporous mesoporous alumina supports have been successfully prepared using a single hard templating approach. Pt nanoparticles, showing similar physico-chemical properties, were homogeneously dispersed throughout the different alumina frameworks as catalytic active phase for drinking water treatment. We demonstrated that careful modification of pore properties of the catalyst (size and connectivity) by pseudomorphic transformation can strongly modulate the reaction rate and selectivity through the limited access to Pt active sites within the alumina porous particles. Specifically, 3-D Ordered Macroporous Pt-Al2O3 catalysts with a high degree of interconnectivity yield to superior catalytic properties (enhanced activity and selectivity) over pure mesoporous counterparts in the hydrogenation of nitrites in water. We found that large pores (240 nm) interconnected with windows (110 nm) alleviate mass transfer limitations and clearly improve NZ selectivity. The findings of this study further suggest the possibility of engineering the pore architecture of the support to fine tune the selectivity for a particular reaction rather than investigating more on tuning the properties of the costly active metallic phase.